(untitled) (Advances in Applied Mathematics and Mechanics, 2010)
In this article, natural convection of a magnetic fluid in a cubic cavity with a heat generating object inside and under a uniform magnetic field is simulated by the lattice Boltzmann method. Results obtained from the present simulations are shown to agree well with our experimental measurements, and reveal more of effects of the magnetic field on the flow and heat transfer of the magnetic fluids.